Experiences and challenges of thorcoscopic lung surgery in the pediatric age group. (November 2015) - Lieber, Justus; Urla, Cristian Ioan; Baden, Winfried; Schäfer, Jürgen; Kirschner, Hans-Joachim; Fuchs, Jörg
Abstract: Background: We report a single-center study of minimally invasive thoracoscopic lung surgery with pediatric patients. Methods: We performed a retrospective analysis of patients who underwent thoracoscopic lung surgery between 2004 and 2013. The procedures were divided into anatomic and non-anatomical lung resections. Results: Seventy-six patients with a mean age of 6.5 years (range: 7 days–17 years) and a mean weight of 11 kg (range: 2.6–56.0 kg) received thoracoscopic lung surgery for tumor metastases (n = 20), sequestration/congenital adenomatoid malformation (19), cysts (12), aspergillomas (7), bullae (5), middle lobe syndrome (3), bronchiectasis (3), emphysema (2), and other reasons (5). Twenty-nine anatomical lung resections (Group I: lobectomies, segmentectomies) and 47 non-anatomical lung resections (Group II: wedge resections, lung tissue-sparing surgery) were performed. In 6 cases, preoperative CT-guided coiling was used to localize the lung lesions. Specimen removal was achieved using a widened (2 cm) trocar site. The operating times of Group I patients were longer compared than those of Group II patients (means: 154 and 68 min, respectively); conversion rates (8 versus 2), chest tube insertion rates (100% versus 51%), and postoperative ventilation (48% versus 13%) also differed. Conclusion: Thoracoscopic anatomical lung resections appear to be safe and effective in infants and children. In congenital lung diseases, the key to success is the intraoperative destruction of space-occupying lesions. Limitations exist in cases with infectious adhesions. Non-anatomical lung resections are technically easier and should remain standard in pediatric surgery. Limitations exist in cases of metastases, which are deep within the parenchyma and are not visible on the lung surface. Highlights: Technical considerations of thoracoscopic surgery in pediatric patients were analyzed. Anatomical lung resections are appear safe and effective in infants and children. Limitations exist due to the small thorax and in cases with infectious adhesions. Non-anatomical lung resections are technically easier and should remain standard. Limitations exsist in cases of metastases deeply within the parenchyma.